Pengaruh Harga, Trust, Kemudahan dan Keamanan Menggunakan E-Commerce Terhadap Keputusan Pembelian (Studi pada Pengguna Shopee Mahasiswa Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam UIN Fatmawati Sukarno Bengkulu) - Muslimah, Anisa; Hak, Nurul; Shar, Aan (Universitas Batanghari Jambi, 2024)
Purchasing decisions are a long process that buyers must go through before they buy a product and continue afterwards. The purpose of this study is to see whether variables such as price, trust, security and convenience variables have an effect on purchasing decisions. object of research for students of class 2020, 20221, and 2023 of the Sharia Economics study program. The object of this research is in the Sharia Economics study program of FEBI UIN Fas Bengkulu. The type of research approach is quantitative associative. Then purposive sampling is used to collect data as many as 100 people who are users of the shopee application. Multiple Linear Regression Analysis is used in the data analysis method. Based on the tests that have been carried out, it is revealed that partially price (X1) has a negative effect and (sig) on purchasing decisions. Then partially the variables of trust (X2), convenience (X3) and security (X4) in using e-commerce have a positive influence (sig) on purchasing decisions.